NFL football : a history of America's new national pastime - Crepeau, Richard C., 1941- (Sport and society., 2020)
"This wide-ranging history synthesizes scholarship and media sources to give the reader an inside view of the television contracts, labor issues, and other off-the-field forces that shaped the National Football League. Historian Richard C. Crepeau shows how Commissioner Pete Rozelle's steady leadership guided the league's explosive growth during the era of Monday Night Football and the Super Bowl's transformation into a mid-winter spectacle. Crepeau also delves into the league's masterful exploitation of media from radio to the internet, its ability to get taxpayers to subsidize team stadiums, and its success in delivering an outlet for experiencing vicarious violence to a public uneasy over the changing rules of masculinity. In this new edition to mark the 100th anniversary of the NFL, Crepeau takes the narrative well into the 21st century. He investigates the intense debate and emotion surrounding Colin Kaepernick, reconsiders Paul Tagliabue's time as commissioner and his role in covering up early information on concussions, and expands his coverage of Roger Goodell emphasizing his relationship with the players"--